The sustainable urban outdoor lighting policy. A case study of Copenhagen - Szlachetko, Katarzyna (Studia Iuridica Toruniensia, 2023)
Copenhagen is a great example of how a city’s policy on sustainable out- door lighting can be shaped even when national law lacks a clear ‘hard’ legal basis for its implementation In this regard, the City of Copenhagen exercises its constitutionally granted legal self-governance, carrying out tasks in the field of urban planning, environmental protection, and the investment and construction process. The goals and measures to achieve them are formalized in complementary strategies and implementing acts that form a coherent vision of development. Copenhagen is an example of a comprehensive (multidisciplinary) approach to the management of the outdoor lighting infrastructure as part of a sustainable policy adjusted to the needs of people, the environment, and the economy, shaped in the city’s climate change adaptation plan, the lighting strategy for the city, and the operational outdoor lighting master plan.